2006
DOI: 10.1084/jem.20051680
|View full text |Cite
|
Sign up to set email alerts
|

Fas-positive T cells regulate the resolution of airway inflammation in a murine model of asthma

Abstract: Persistent airway inflammation, mucus production, and airway hyperreactivity are the major contributors to the frequency and severity of asthma. Why lung inflammation persists in asthmatics remains unclear. It has been proposed that Fas-mediated apoptosis of inflammatory cells is a fundamental mechanism involved in the resolution of eosinophilic airway inflammation. Because infiltrating eosinophils are highly sensitive to Fas-mediated apoptosis, it has been presumed that direct ligation of Fas on eosinophils i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 56 publications
9
84
0
Order By: Relevance
“…To investigate how Fas-FasL interactions occur and regulate the resolution of airway inflammation in vivo, we used a previously described murine model of allergic airway disease and mice with abnormalities in the FasL signaling pathway (8,21). We found that FasL deficiency (Gld) led to a delayed resolution of airway inflammation similar to our previous observations.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…To investigate how Fas-FasL interactions occur and regulate the resolution of airway inflammation in vivo, we used a previously described murine model of allergic airway disease and mice with abnormalities in the FasL signaling pathway (8,21). We found that FasL deficiency (Gld) led to a delayed resolution of airway inflammation similar to our previous observations.…”
supporting
confidence: 57%
“…Duez and colleagues (7) have shown that Fas deficiency delays the resolution of airway hyperresponsiveness (AHR) after allergen sensitization and challenge. Fas-deficient mice have a delayed resolution of airway inflammation, and mice with Fas deficiency only on T cells developed a prolonged phase of airway inflammation, mucus production, and airway hyperreactivity (8). This prolonged airway inflammation phase correlated with decreased IFN-g production by Fas-deficient T cells.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…IFN-γ can contribute to resolution by upregulating Fas (CD95) expression on lymphocytes to increase their rate of apoptosis 41 . Mice lacking IFN-γ or Fas exhibit defective resolution of inflammation in experimental models of asthma 42,43 . As an IFN-γ-neutralizing antibody partially blocked RvE1-mediated resolution, IFN-γ is important for resolution of airway inflammation in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fas/FasL (CD95/CD95L) signaling plays a major role in the physiological regulation of T cell homeostasis (38), and Fas deficiency on T cells has been associated with the development of long-term allergic airway disease in mice (51). However, FasL/Fas has never been associated with the function of Tregs, including the GZ-A-and GZ-B-expressing Tr1 (28).…”
Section: Tregs and Ccr4mentioning
confidence: 99%